Ultimate biaxial bending resistance of H-section steel members under different loading paths. (January 2023) - Cheng, Xin; Du, Huibo; Shi, Xiaopeng; Mansour, Mohamad
Abstract: In order to explore the ultimate biaxial bending performance of H-section steel members under different loading conditions, we conduct a comprehensive parametric study on H-section members with different axial force ratios, web and flange width-to-thickness ratios, and loading angles. Material and geometric nonlinearity are considered, and previous laboratory test results validate the finite element models. A criterion for determining the ultimate state of biaxial bending members is proposed based on the elastic–plastic stability theory. The ultimate biaxial capacity of the members subjected to monotonic biaxial bending and axial force is analyzed, and biaxial moment ultimate interaction curves are obtained by least square fitting. Furthermore, the influences of four different hysteretic protocols on the hysteretic behavior of the members are investigated, and the applicability of the monotonic biaxial moment limit interaction curve to the cyclic loading model is verified. A design equation for predicting the ultimate capacity of the members is proposed, considering the hardening effect of the material and the interaction effect of the plate. The proposed approach can predict the ultimate capacity of H-section biaxial bending members. The method is not limited by section classification and loading protocol and has universal applicability. Highlights: A criterion for determining the ultimate state of H-shaped steel members subjected to biaxial bending. The ultimate state development process of H-shaped steel members under monotonic loading. Four complex cyclic loading systems, including the BL, REC, ROM, CRU, were selected to conduct the ultimate state analysis. The similarities and differences of ultimate state between monotonic loading and cyclic loading. Biaxial ultimate interaction curves accurately predict ultimate bidirectional bending moment of members.